Pengaruh Lingkungan Eksternal Individu dan Mutu Layanan Pendidikan terhadap Keputusan Pemilihan Perguruan Tinggi di Kota Makassar - Muhammad Azis; Chalid Imran Musa (Jurnal Aplikasi Manajemen, 2012)
The objective of this research is to find out student’s response index and the influences of the individual extern environment and education services quality toward graduate choice decision on the Makassar. The categorical of research methodology is explanatory survey and data collected technique by using questionnaires to prediction student’s response on justification research variables, observation technique to have the use of student’s contact on the graduate and the sample size for the research criteria are 116 students.The result of this research to answer the hypothesis conceptual paradigm research with path analysis showed the individual extern environment and services education quality influenced and significant both partial or simultaneously toward graduate choice decision on the Makassar.Keywords: external enviroment, education services quality, garaduate choise